Odpowiedzi

2009-11-15T13:25:52+01:00
A) 2y-(3x+y)=3y+5
2y-3x-y=3y+5
y-3x-3y=5
-3x-2y=5
b) y+5x/2=y-1 /*2
y+5x=2y-2
5x-y=-2
2009-11-15T13:28:45+01:00
A) 2y-(3x+y)=3y+5
2y-3x-y=3y+5
y-3x-3y=5
-2y-3x=5
b)y+5x/2=y-1 / x2
y+5x=y-2
y+5x-y=-2
5x=-2
Najlepsza Odpowiedź!
2009-11-15T13:29:44+01:00
A) 2y-(3x+y)=3y+5 /opuszczamy nawias
2y - 3x - y = 3y + 5 /-3y
y - 3y - 3x = 5
-2y - 3x = 5
-2y = 3x + 5 /: (-2)
y = -1,5x - 2,5

b) (y + 5x)/2 = y - 1 /*2
y + 5x = 2y - 2 /-y /+2 /-5x
2 = y - 5x
lub jak kto woli:
y - 5x = 2
y=5x + 2

Pozdrawiam ;)